Modeling the Performance of Civil Servants in the Tegal Regency Government - Agus Priono; Amir Fikri; Maya Maria (Cv. Syntax Corporation Indonesia, 2026)
This study aims to examine the effect of workload, compensation, and training on the performance of Civil Servants (ASN), with job satisfaction as a mediating variable among ASN in the Tegal Regency Government. Using a quantitative approach with causal explanatory design, data were collected through questionnaires distributed to 200 ASN respondents selected using purposive sampling technique. The validity test results showed that all indicators had loading factor values above 0.60 with CR > 1.96 and p-value < 0.05, while the reliability test using Cronbach's Alpha produced values above 0.90 for all variables (workload 0.926, compensation 0.926, training 0.925, job satisfaction 0.916, performance 0.943). The Goodness of Fit test indicated a fit model (Chi-Square 1245.321, p = 0.061; CMIN/DF = 1.742; GFI = 0.91; RMSEA = 0.047). The results show that workload has a negative and significant effect on job satisfaction (CR = 2.984; p = 0.003) and performance (CR = 3.284; p = 0.001). Compensation has a positive and significant effect on job satisfaction (CR = 3.468; p = 0.001) and performance (CR = 3.112; p = 0.002). Training has a positive and significant effect on job satisfaction (CR = 3.873; p = 0.004) and performance (CR = 3.657; p = 0.000). Job satisfaction has a positive and significant effect on ASN performance (CR = 3.194; p = 0.001). Furthermore, job satisfaction mediates the relationships between workload, compensation, and training on performance with indirect effect values of 0.338 (p = 0.000), 0.297 (p = 0.002), and 0.365 (p = 0.000) respectively.